Switzerland : Report on Observance of Standards and Codes; Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper focuses on the observance of standards and codes on fiscal transparency for Switzerland. The assessment reveals that the fiscal role of the executive and legislative branches of government, and the legal framework for the management of federal public finances, are clearly defined. The federal budget process is governed by a precise legal framework. A coherent medium-term fiscal framework provides a clear context for budget decisions. The accuracy of macroeconomic forecasts compares favorably with private sector counterparts. There are some areas, however, where further measures could be considered.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet